Selection on female reproductive schedules in the marula fly, Ceratitis cosyra (Diptera: Tephritidae) affects dietary optima for female reproductive traits but not lifespan - Malod, Kevin; Archer, C. Ruth; Hunt, John; Nicolson, Susan W.; Weldon, Christopher W. (Frontiers in Insect Science, 2023)
Introduction A changing environment can select on life-history traits and trade-offs in a myriad of ways. For example, global warming may shift phenology and thus the availability of host-plants. This may alter selection on survival and fertility schedules in herbivorous insects. If selection on life-histories changes, this may in turn select for altered nutrient intake, because the blend of nutrients organisms consume helps determine the expression of life-history traits. However, we lack empirical work testing whether shifts in the timing of oviposition alter nutrient intake and life-history strategies. Methods We tested in the marula fruit fly, Ceratitis cosyra, how upward-selection on the age of female oviposition, in comparison with laboratory adapted control flies, affects the sex-specific relationship between protein and carbohydrate intake and life-history traits including lifespan, female lifetime egg production and daily egg production. We then determined the macronutrient ratio consumed when flies from each selection line and sex were allowed to self-regulate their intake. Results Lifespan, lifetime egg production and daily egg production were optimised at similar protein to carbohydrate (P:C) ratios in flies from both selection lines. Likewise, females and males of both lines actively defended similar nutrient intake ratios (control =1:3.6 P:C; upward-selected = 1:3.2 P:C). Discussion Our results are comparable to those in non-selected C. cosyra, where the optima for each trait and the self-selected protein to carbohydrate ratio observed were nearly identical. The nutrient blend that needs to be ingested for optimal expression of a given trait appeared to be well conserved across laboratory adapted and experimentally selected populations. These results suggest that in C. cosyra, nutritional requirements do not respond to a temporal change in oviposition substrate availability.